Inhibition of Acetylcholinesterase and Amyloid-β Aggregation by Piceatannol and Analogs: Assessing In Vitro and In Vivo Impact on a Murine Model of Scopolamine-Induced Memory Impairment - Yi-Yan Sie; Liang-Chieh Chen; Cai-Jhen Li; Yu-Hsiang Yuan; Sheng-Hung Hsiao; Mei-Hsien Lee; Ching-Chiung Wang; Wen-Chi Hou (MDPI AG, 2023)
Currently, no drug is effective in delaying the cognitive impairment of Alzheimer's disease, which ranks as one of the top 10 causes of death worldwide. Hydroxylated stilbenes are active compounds that exist in fruit and herbal plants. Piceatannol (PIC) and gnetol (GNT), which have one extra hydroxyl group in comparison to resveratrol (RSV), and rhapontigenin (RHA) and isorhapontigenin (isoRHA), which were metabolized from PIC in vivo and contain the same number of hydroxyl groups as RSV, were evaluated for their effects on Alzheimer's disease-associated factors in vitro and in animal experiments. Among the five hydroxylated stilbenes, PIC was shown to be the most active in DPPH radical scavenging and in inhibitory activities against acetylcholinesterase and amyloid-β peptide aggregations, with concentrations for half-maximal inhibitions of 40.2, 271.74, and 0.48 μM. The different interactions of the five hydroxylated stilbenes with acetylcholinesterase or amyloid-β were obtained by molecular docking. The scopolamine-induced ICR mice fed with PIC (50 mg/kg) showed an improved learning behavior in the passive avoidance tests and had significant differences (p < 0.05) compared with those in the control group. The RHA and isoRHA at 10 μM were proven to stimulate neurite outgrowths in the SH-SY5Y cell models. These results reveal that nutraceuticals or functional foods containing PIC have the potential for use in the treatment of neurodegenerative disorders.